Pengaruh Website Cinema 21 Terhadap Loyalitas Pengunjung (Studi Kasus Cinema 21 Kota Batam) - Rika Harman (Computer Based Information System Journal, 2015)
Websites began to be known in Indonesia around 1998, in which only large companies can afford to have it. At that time, the website is a technology that is quite expensive to own. So many entrepreneurs and manufacturers discourage them to be able to have this media campaign. The steps of making a web services provider that offers low prices make these companies desire to have a cheap website just be a dream. That was then, now there are virtually billions of web pages that enliven the virtual world. Most of these are commercial web site that is business and commerce. Apparently the media campaign in the form of a website is very important in the business world. The proof lately many large and small businesses have used the website as a medium of promotion in marketing products or services. Websites that not only functions as a promotional tool but also as an effort to increase the prestige (prestige) of a company has made ​​a lot of bold entrepreneurs to pay high enough to have this online media. Often we ask questions when we attended seminars that discuss about the website, "Why have a website? Though a company would have been nice about her products mepunyai brochures or marketing experience in marketing". This question is very good, but we all know that the website can be accessed from all over the world so it can be viewed by potential customers 24 hours a day, 365 days a year, it's certainly not going to be possible with marketing brochures and no matter how great, because there is no marketing who can distribute flyers throughout the country or no marketing is able to work 24 hours a day and 365 a year. But through a website product a company will be seen by hundreds of millions of people online every day to use email, chat, search for information, buy products in online stores, even mere entertainment. The majority of Internet users (young people and businessmen) would expect a company to have a website. It is now common people say, "Good product, want to see on the internet." or "what company it is, the website address where?. Website accessed much more quickly, more easily understood and effective in terms of cost when compared to other media. Via a website we can put articles, pictures, or any sort of detailed product information and even online stores online map that can guide us to our own office (with the help of Google Map example). websites can be an important part of company's promotional and marketing strategies. Creation website marketing needs to be a serious agenda. More than that can increase the reliability of the company's website.